Promoting indigenous wild edible fruits to complement roots and tuber crops in alleviating vitamin A deficiencies in Uganda - Musinguzi, E.; Kikafunda, J. K.; Kiremire, B. T. (Proceedings of the 13th ISTRC Symposium, 2007)
Micronutrients lack in most of the foods eaten by majority of Ugandans and consequently, micronutrient malnutrition is so high in Uganda. Due to low incomes, many people cannot afford to buy exotic sources of these nutrients. Local sources of nutrients should be sought, as a food-based approach to complement supplementation and fortification efforts that currently leave a lot of ‘hard to reach people’not served. Indigenous fruits could be such nutrient sources. Unfortunately the nutrient content for most of them is not known. Chemical analyses were carried out on Physalis minima and Carissa edulis fruits and indicated that they are rich sources of micronutrients especially minerals. These indigenous fruits compared well with the exotic ones (mangoes, paw paws and Physalis peruviana) in nutrient content.